2021
DOI: 10.3390/polym13040498
|View full text |Cite
|
Sign up to set email alerts
|

Green Procedure for Aerobic Oxidation of Benzylic Alcohols with Palladium Supported on Iota-Carrageenan in Ethanol

Abstract: The search for selective heterogeneous catalysts for the aerobic oxidation of alcohols to ketones and aldehydes has drawn much attention in the last decade. To that end, different palladium-based catalysts have been proposed that use various organic and inorganic supports. In addition, supports that originate from a biological and renewable source that is also nontoxic and biodegradable were found to be superior. We heterogenized palladium chloride or acetate complexes with triphenylphosphine trisulfonate on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…As noted above, the use of i-Pd(OAc) 2 (TPPTS) 2 xerogel as the heterogeneous catalyst in the aerobic oxidation of benzylic alcohols in ethanol led to a reduction in the palladium complex and the formation of palladium nanoparticles during the reaction [21]. We previously report edthat the ratio of Pd(0)/Pd(II) was increased following 24 h of the reaction, based on XPS analysis, i.e., 46% of the Pd(II), derived from Pd(OAc) 2 , was reduced to its metallic form during 24 h of reaction [21]. Thus, we have already demonstrated that following 24 h of reaction the formation of palladium nanoparticles is enhanced.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As noted above, the use of i-Pd(OAc) 2 (TPPTS) 2 xerogel as the heterogeneous catalyst in the aerobic oxidation of benzylic alcohols in ethanol led to a reduction in the palladium complex and the formation of palladium nanoparticles during the reaction [21]. We previously report edthat the ratio of Pd(0)/Pd(II) was increased following 24 h of the reaction, based on XPS analysis, i.e., 46% of the Pd(II), derived from Pd(OAc) 2 , was reduced to its metallic form during 24 h of reaction [21]. Thus, we have already demonstrated that following 24 h of reaction the formation of palladium nanoparticles is enhanced.…”
Section: Resultsmentioning
confidence: 89%
“…It was thus assumed that the impregnation duration time enhanced/reduced the palladium activity due to two opposing effects: (1) The reduction of palladium and formation of nanoparticles that accelerated the reaction, and (2) The growth of palladium nanoparticles and the formation of aggregates, which reduced the palladium outer surface area and may have decreased its activity. Therefore, our hypothesis was that until 24 h the palladium complex was reduced by the ethanol, and, in turn, that the conversion rate increased due to the formation of Pd(0) and the increase in the surface area of the palladium [21]. However, it appears that after 24 h the nanoparticles were agglomerated and, therefore, the outer surface area of the palladium was reduced, hence the reduction of the activity towards benzyl alcohol oxidation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…29 Thus, the investigation is initiated with the oxidation of benzyl alcohol (Figure 1) in three representative solvents with different polarities: ethanol, ethyl acetate, and hexane (Table 1). The conversion of the reactions in ethanol has already been studied, 27 and those results were used as comparative reference data to assess the results for the other solvents. At first a simple Pd(OAc) 2 was used as a catalyst without or with the addition of sodium carbonate as cocatalyst (entries 1 and 2, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…As previously noted, when ethanol was used as the solvent, the palladium complex was reduced and nanoparticles formed. 27 Moreover, the formation of these nanoparticles was suggested as the reason that higher conversion yields were obtained with the recycled catalyst. Thus, the i-Pd(OAc) 2 (TPPTS) 2 also underwent TEM analyses after reactions in hexane and ethanol (Figure 7).…”
Section: Resultsmentioning
confidence: 99%